2012
DOI: 10.1002/j.0022-0337.2012.76.10.tb05394.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pairing Revisited: A Study at the University of Malaya, Malaysia

Abstract: This study is part of ongoing educational research conducted by the Department of Conservative Dentistry, University of Malaya, Malaysia, to evaluate the perception of clinical pairing. A thirteen-question survey was distributed to 148 dental students after they had experienced four-handed dentistry. The objectives were to identify the advantages, disadvantages, and the acceptance of the implementation of clinical pairing from the students' point of view. The responses from the open-ended questions were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…This partnership could also be jeopardized if a member of the pair, especially the assistant, decided to disappear from the clinical situation, thereby defeating the purpose of clinical pairing. 12 Usually clinical pairing is carried out in an obligatory fashion. It would be part of the curriculum and students' pairing would be arranged by dental school or department administrations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This partnership could also be jeopardized if a member of the pair, especially the assistant, decided to disappear from the clinical situation, thereby defeating the purpose of clinical pairing. 12 Usually clinical pairing is carried out in an obligatory fashion. It would be part of the curriculum and students' pairing would be arranged by dental school or department administrations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that students' performance can be enhanced through interdependence between students and the prospect of being able to learn from each other and exchange of knowledge between the operator and assistant can improve treatment procedures. 12 A recent study done in the United States assessing the satisfaction among students regarding pairing and implementation of 4-handed clinical training showed an overall satisfaction rate of 70.1%, with a positive impact on students clinical knowledge and experience. 9 Initially, dental students might find it challenging to adjust to a 4-handed clinical setting, which might lessen the stipulated benefits of this learning method.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations